2017
DOI: 10.3844/ajassp.2017.302.308
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Nere Pod (<i>Parkia Biglobosa</i>) for the Improvement of Mechanical Properties of Soils

Abstract: Buildings made of unbaked clay have some advantage in terms of production cost. However, they have some inconveniences concerning their mechanical performance, particularly their resistance to weather. The objective of this study is to minimize these disadvantages and to maximize the benefits of such buildings to make them more viable. For this purpose, a method based on a traditional practice where the néré pod is utilized as a color wash, as well as, a binder is used. In the first case (color wash), it is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Keita's work in 2014 showed that the incorporation of néré pods in the clay + sand mixture makes it possible to increase the material mechanical resistance [10]. Similar results were obtained by Banakinao in 2017 on earth-based bricks, boiled skins and banana leaves as well as néré tannins [11].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Keita's work in 2014 showed that the incorporation of néré pods in the clay + sand mixture makes it possible to increase the material mechanical resistance [10]. Similar results were obtained by Banakinao in 2017 on earth-based bricks, boiled skins and banana leaves as well as néré tannins [11].…”
Section: Introductionmentioning
confidence: 52%
“…A complete modelization of bidirectional transfer in the samples associated with hot wire model makes it possible to use the entire thermogram between 0 s and 180 s to estimate the thermal conductivity using (11) [13,14].…”
Section: Thermal Conductivity Estimationmentioning
confidence: 99%
“…Bridelia (Figure 5) is one of the plants highly rich in tannin, like the leaf sheath of sorghum, the bark of false logwood and the pod of Nere [14] [15] [16] [17].…”
Section: Tannic Extraction Methodologymentioning
confidence: 99%
“…Therefore, it is of interest to investigate alternative roof coverings that are efficient and economic. The present study is within the framework of promoting the use of local and environment-friendly materials (Banakinao et al, 2017;Lolo et al, 2017;Banakinao et al, 2016;Drovou et al, 2015;Keita et al, 2014;Sorgho et al,2014;Pasch and Pizzi, 2002;Lefeu and Francy, 1999). The new design of roof coverings proposed in this study uses layers of bituminous plywood, at different proportions and different compositions, with fibers of cotton, as intermediate support between the wood frames and the roofing tiles, to guarantee the waterproofing of the roof.…”
Section: Introductionmentioning
confidence: 99%